Structural evolution of kaolinite in muddy intercalation under microwave heating. (12th October 2021) - Hu, Qijun; Yong, Qin; He, Leping; Gu, Yucheng; Zeng, Junsen
Abstract: The failure of muddy intercalation in the slope is mainly due to the clay minerals which mainly contains the kaolinite. This study investigates the structural evolution of kaolinite in muddy intercalation exposed to the microwave heating of 300 °C–800 °C by evaluating the uniaxial compressive strength, morphology, mineralogical composition, and water stability. Results show that the crystal structural evolution of kaolinite can be divided into four stages, which are 300 °C–400 °C, 400 °C–500 °C, 500 °C–700 °C, and 700 °C–800 °C. The kaolinite undertakes the thermal expansion, dehydroxylation-induced crack, kaolinite-metakaolinite transition, and two-step transition of metakaolinite - silica spinel ( γ -alumina) - mullite. The mechanical performance increasing consists of three stages. At 300 °C–400 °C, the uniaxial compressive strength increases about 38.7% due to thermal expansion. At 400 °C–700 °C, the uniaxial compressive strength is unchanged due to the balance between the positive side due to thermal expansion and semi-liquid metakaolinite and the negative side due to the dehydroxylation-induced crack propagation. At 700 °C–800 °C, the re-increase of 35.8% is mainly due to the two-step transition of metakaolinite-silica spinel ( γ -alumina)-mullite. Water leaching test shows that the kaolinite over 500 °C present well integrity.